RETRACTED: Reproductive attitudes: Gender aspect - Kamarova T.A.; Tonkikh N.V.; Markova T.L. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001